Macroeconomic policies for growth - Ricardo Ftrench-Davis (CEPAL Review, 1996)
This article analyses the interrelation between the macro-economic framework and growth. After reviewing the recent macroeconomic environment, highlighting progress and shortcomings, it focuses on the implications of the existence of gaps between production capacity and its degree of utilization or effective demand; the way in which persistent disparities in this respect affect the speed of expansion of the production frontier is illustrated by examples from the 1980s and 1990s. It then reviews economic policies that affect the degree of proximity between the production frontier and effective demand, with particular reference to the cases of anti-inflationary policies and external shocks.